Does Climate Awareness Lead to Climate Action? A Study on Adults in Malawi - Sato, Fred; Park, Jonghwi (WIMAYA, 2024)
The study examined the general understanding of climate change among Malawian adults (n=601) and its impact on their climate-related actions. Leveraging the knowledge-attitude-behavior theory, it assessed their awareness, readiness to act, and actual practices against climate change. The results showed that 40 percent of participants have a high awareness of climate change, with varied levels of awareness observed across the spectrum. Educational attainment (p=.000) emerged as the sole significant predictor of climate change awareness. Although 68 percent of respondents showed a willingness to act, the study found that some actions are more prevalent than others. The research identified a statistically significant relationship between climate change awareness and action (R=0.187, p<.001). These findings contribute to the ongoing discussion on the role of climate change awareness and its influence on action, offering valuable perspectives for policymakers in developing climate change awareness programs and education.